Functional outcome of displaced mid shaft clavicular fractures treated by plate fixation: a prospective observational study - Ebrahim, Junaid; Variyathodi, Abdul Asraf; Thody Uppil Thody, Mohamed Shakeeb Kannan; Chandrasekharan, Nithin (International Journal of Research in Orthopaedics, 2021)
Background: Clavicle fractures are one of the commonest injuries to the shoulder girdle. Traditionally these fractures are treated conservatively. This study was to assess the functional outcome of displaced mid shaft clavicular fractures treated with plate fixation. Methods: This was a single center prospective observational study conducted at department of orthopaedics M.E.S medical college Perinthalmanna between the period January 2018 to December 2018 in patients with displaced mid shaft clavicle fractures treated by plate fixation. Out of 51 patients 35 patients were males and 16 were females with mean age of 37.7 years (range 19-59). All patients included in this study were included under Allman group 1. All Patients were treated with plate fixation. Post op follow done at 1 1/2 ,3 and 6 months. During follow up clinical and radiological union were checked. Final functional outcome was assessed at 6 months follow up by Constant-Murley Score. Results: Out of 51 patients with displaced mid shaft clavicle fractures treated with plate fixation 43 patients (84.3%) showed excellent functional outcome 8 patients (15.7%) showed good functional outcome. None of the patients showed moderate or poor outcome. The radiological union was attained at 9.35 weeks. No complications in 83.4% of patients. Conclusions: Mid shaft clavicle fractures are more common in young males sustaining high energy trauma, and those fractures treated with plate fixation has a better functional outcome in terms of pain relief, activities of daily living and range of motion.